The Oskar Fehr Lecture - Weiss, J. S. (Klinische Monatsblätter für Augenheilkunde, 2016)
Purpose: The first Oskar Fehr lecture is given in honour of Professor Fehr, a well respected ophthalmologist, who was head physician of the Department of Eye Diseases at the Rudolf Virchow Hospital from 1918. He practiced there until 1938, when he was forbidden to enter the clinic because he was Jewish and subject to the anti-Semitic laws that were instituted after the rise of the Nazi party. Dr. Fehr escaped to Great Britain, where he practiced ophthalmology into his eighties. He was the first to distinguish between granular corneal dystrophy, lattice corneal dystrophy and macular corneal dystrophy. The topic of the first Oskar Fehr lecture is Schnyder corneal dystrophy (SCD), an autosomal dominantly inherited corneal dystrophy associated with abnormal cholesterol deposition in the cornea. Methods: The clinical, histopathologic and genetic findings of 115 individuals with SCD followed over 18 years are discussed. The impact of systemic cholesterol metabolism on other diseases is reviewed. Results: Corneal findings in SCD are predictable on the basis of patient age. All patients develop progressive corneal haze because of abnormal deposition of corneal lipid, but only half of patients with SCD have evidence of corneal crystals. The prior name for this disease, Schnyder crystalline corneal dystrophy, led me to create the International Committee for the Classification of Corneal Dystrophies, in order to create a more up-to-date and accurate nomenclature for SCD and other corneal dystrophies. The name was then changed to Schnyder corneal dystrophy. Histopathology of excised SCD corneas demonstrates abnormal deposition of only HDL cholesterol. Mutations in the UBIAD1 gene result in SCD. Three dimensional protein modeling shows that mutations result in impaired vitamin K synthesis, suggesting a common link between vitamin K and cholesterol metabolism. UBIAD1 mutations are associated with other diseases, such as bladder carcinoma and Parkinsonʼs disease like findings in Drosophila. Conclusions: Studies of the cause of SCD have led to the discovery of UBIAD1 gene mutations; further work has demonstrated the systemic importance of this gene. The association of vitamin K metabolism and cholesterol metabolism may give us insight into other diseases, so that SCD research may also have implications beyond ophthalmology.
Keywords: corneal dystrophy; lipid; genetic diseases; Schnyder corneal dystrophy; Schnyder crystalline corneal dystrophy; genetic mutations